Social representations of cancer in patients from Medellín, Colombia: a qualitative study - Higuita-Gutiérrez, Luis Felipe; Estrada-Mesa, Diego Alejandro; Cardona-Arias, Jaiberth Antonio (Frontiers in Sociology, 2023)
Background Cancer has different explanatory theories that address its etiology and treatment. It is usually associated with pain and suffering. Recently, new technologies, knowledge, and therapies have been developed, which may have transformed the classic social representations of the disease. This study aimed to understand the social representations (SRs) of cancer in patients from Medellín, Colombia. Methods This study used a grounded theory in 16 patients with cancer. The information was collected between June 2020 and May 2021. Information was analyzed following the open, axial, and selective coding stages. Results SRs of cancer at the time of diagnosis evoke negative connotations. However, cancer is redefined as a positive event as the clinical course of the disease progresses, and patients interact with health professionals and respond to treatment. The resignification of the disease depends on the etiological models of the patients, which include genetic, socio-anthropological, psychosocial, and psychogenic factors. In line with the SRs of etiology, patients seek out treatments complementary to the biomedical ones that can be socio-anthropological and psychogenic. Conclusion In this group negative representations about cancer persist, this way of understanding the disease is determined by the convergence of cultural meanings and personal experiences. The causal representation is connected to the actions and willingness of the patients to face their diagnosis. In this sense, two categories stand out: the first expresses that cancer is the consequence of a body subjected to excessive productivity; the second subsumes a psychogenic predisposition caused by the context where the ideology of happiness appears to be a social norm. This double saturation in which an individual is immersed results in new burdens that are not visible to caregivers and healthcare workers.